Proof Of Erasability for Ensuring Comprehensive Data Deletion in Cloud Computing - Paul, Mithun; Saxena, Ashutosh (Recent Trends in Network Security and Applications, 2010)
In a typical cloud environment the client will be storing his data with a provider and paying as per the usage time. At the end of the contract the client, as the data owner, may like to see that the data should be properly shredded in the provider storage. In this paper we provide a scheme for Proof of Erasability (POE) for a client that a target data is completely destructed or is irreversibly rendered useless. The destruction of the data is achieved by a comprehensive destruction algorithm which systematically modifies the most significant bit(s) of every data chunk thereby making the data irrecoverably destructed and refuting any concerns on privacy and security.